Expression and Function of the Endocannabinoid System in the Retina and the Visual Brain - Jean-François Bouchard; Christian Casanova; Bruno Cécyre; William John Redmond (Neural Plasticity)
Endocannabinoids are important retrograde modulators of synaptic transmission throughout the nervous system. Cannabinoid receptors are seven transmembrane G-protein coupled receptors favoring Gi/o protein. They are known to play an important role in various processes, including metabolic regulation, craving, pain, anxiety, and immune function. In the last decade, there has been a growing interest for endocannabinoids in the retina and their role in visual processing. The purpose of this review is to characterize the expression and physiological functions of the endocannabinoid system in the visual system, from the retina to the primary visual cortex, with a main interest regarding the retina, which is the best-described area in this system so far. It will show that the endocannabinoid system is widely present in the retina, mostly in the through pathway where it can modulate neurotransmitter release and ion channel activity, although some evidence also indicates possible mechanisms via amacrine, horizontal, and Müller cells. The presence of multiple endocannabinoid ligands, synthesizing and catabolizing enzymes, and receptors highlights various pharmacological targets for novel therapeutic application to retinal diseases.